2021
DOI: 10.1038/s41467-021-21831-y
|View full text |Cite
|
Sign up to set email alerts
|

Fragility of surface states in topological superfluid 3He

Abstract: Superfluid 3He, with unconventional spin-triplet p-wave pairing, provides a model system for topological superconductors, which have attracted significant interest through potential applications in topologically protected quantum computing. In topological insulators and quantum Hall systems, the surface/edge states, arising from bulk-surface correspondence and the momentum space topology of the band structure, are robust. Here we demonstrate that in topological superfluids and superconductors the surface Andre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 61 publications
0
43
0
Order By: Relevance
“…These are important capabilities for realising magnon-based devices 27 – 32 . To access phenomena such as quantum entanglement, few-magnon operations can be implemented using nano-fluidic confinement and ultra-sensitive NMR techniques 33 , 34 . We emphasise that similar physical phenomena including quasiparticle Bose-Einstein condensation and the emergence of time crystals can be accessed in certain solid-state room-temperature systems, for example based on magnons in YIG films 35 42 .…”
Section: Discussionmentioning
confidence: 99%
“…These are important capabilities for realising magnon-based devices 27 – 32 . To access phenomena such as quantum entanglement, few-magnon operations can be implemented using nano-fluidic confinement and ultra-sensitive NMR techniques 33 , 34 . We emphasise that similar physical phenomena including quasiparticle Bose-Einstein condensation and the emergence of time crystals can be accessed in certain solid-state room-temperature systems, for example based on magnons in YIG films 35 42 .…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that in the planar aerogel the anisotropy of scattering of 3 He quasiparticles is analogous to that in a narrow gap, and in the recent experiments with 3 He-A in a very thin gap [54] it was suggested that the suppression of the superfluid transition in the presence of solid paramagnetic 3 He on the walls is partially due to the magnetic scattering.…”
Section: Discussionmentioning
confidence: 98%
“…In nanofluidic geometries, atomically smooth silicon surfaces can be used to reach a specularity close to its maximum value [93]. Additionally, the specularity of the walls in these geometries could be tuned in-situ with the amount of 4 He atoms covering the surface [40]. The maximum specularity (S = 0.98) was obtained with a coverage of 3-4 atomic layers of 4 He, which is enough to form a superfluid 4 He layer on the surface.…”
Section: Boundary Scatteringmentioning
confidence: 99%
“…In the present work, we propose a novel architecture for superfluid optomechanics, based on engineered nanostructures allowing a better control over superfluid phonon propagation, preserving superfluid 4 He's exceptional intrinsic properties, and leading to enhanced quality factors and coupling strengths. Exploiting recent progress in quantum nanofluidics, concerning the confinement at the nanoscale of quantum fluids (liquid helium-4 [27][28][29][30][31][32][33][34] and liquid helium-3 [29,[35][36][37][38][39][40]), one can form a nanoscale cavity of typically hundreds of nm in height, and tens of µm in width defining the boundaries of a picogram or femtogram scale superfluid acoustic resonator [30][31][32]. Such superfluid acoustic resonator could be formed by means of a microsale hollow volume within a glass or silicon substrate.…”
Section: Introductionmentioning
confidence: 99%